Fast Quantification of S-adenosyl-L-methionine in Dietary Health Products Utilizing Reversed-Phase High-performance Liquid Chromatography: Teaching an Old Method New Tricks - Liou, Jing-Ru; Chuang, Li-Yeh; Yang, Yuan-Han; Wu, Tung-Ying; El-Shazly, Mohamed; Wu, Shyh-Jong; Hsieh, Tusty-Jiuan; Wu, Yang-Chang; Wu, Jiumn-Yih; Chang, Fang-Rong (Planta Medica, 2014)
S-adenosyl-L-methionine is a ubiquitous methyl donor in living bodies. It is known to participate in several physiological processes including homocysteine metabolism and glutathione synthesis regulation, and cellular antioxidant mechanism. S-adenosyl-L-methionine containing dietary supplements has been prescribed recently for the treatment of depression, arthritis, and liver diseases with encouraging results. The development of an efficient analytical protocol for S-adenosyl-L-methionine containing dietary supplements is crucial for maintaining product quality and consumer health. In this study, the S-adenosyl-L-methionine content of several yeast products and commercial healthy food product samples was quantitatively analyzed utilizing HPLC. The chromatographic separation was achieved on a reversed-phase column and 2 % acetonitrile with a 98 % ammonium-acetate mobile phase under pH 4.5, with a flow rate of 1.0 mL/min. The wavelength used for detection with the UV detector was 254 nm. The total analysis time was short and the target compound showed a well-defined peak. The correlation coefficient of the regression curve showed good linearity and sensitivity with r = 0.999. All experiments were replicated five times and the relative standard deviations as well as the relative error values were all less than 3 %. Moreover, the achieved precision and accuracy values were high with 97.4–100.9 % recovery. Qualitative determination of S-adenosyl-L-methionine in the tested products was achieved using NMR and LC-MS techniques. The developed protocol is robust, fast, and suitable for the quality control analysis of yeast and commercial S-adenosyl-L-methionine products.
Keywords: HPLC; S-adenosyl-L-methionine; Saccharomyces cerevisiae (yeast); LC-MS